2006
DOI: 10.2337/dc06-0407
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Control Influences Glomerular Filtration Rate and Its Prediction in Diabetic Subjects

Abstract: OBJECTIVE -Hyperglycemia increases glomerular filtration rate (GFR), but the influence of HbA 1c (A1C) on GFR and GFR's prediction by recommended equations remains to be determined.RESEARCH DESIGN AND METHODS -In 193 diabetic patients, we searched for an association between A1C and isotopically measured GFR (51Cr-EDTA) and their predictions by the Cockcroft and Gault formula (CG) and the modification of diet in renal disease (MDRD) equation. Their accuracy for the diagnosis of moderate (GFR Ͻ60 ml/min per 1.73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 31 publications
4
26
0
3
Order By: Relevance
“…Jin et al indicated a similar finding to ours; glomerular hyperfiltrators exist among Japanese subjects with type 2 diabetes without proteinuria or hypertension, and they were characterized by higher HbA 1C than normofiltrators (18). A significant linear correlation of HbA 1C with estimated/measured GFR was shown (19,20). It is likely that chronic hyperglycemia may act through a mechanism that involves increased nitric oxide generation and/or action, leading to an increase in GFR (21).…”
Section: Variables Affecting the Gfr Slope: Baseline Gfr And Hba 1csupporting
confidence: 69%
“…Jin et al indicated a similar finding to ours; glomerular hyperfiltrators exist among Japanese subjects with type 2 diabetes without proteinuria or hypertension, and they were characterized by higher HbA 1C than normofiltrators (18). A significant linear correlation of HbA 1C with estimated/measured GFR was shown (19,20). It is likely that chronic hyperglycemia may act through a mechanism that involves increased nitric oxide generation and/or action, leading to an increase in GFR (21).…”
Section: Variables Affecting the Gfr Slope: Baseline Gfr And Hba 1csupporting
confidence: 69%
“…Increases in blood glucose can impair functions of the glomerulus (filtration, permeability, and renal regulation of blood pressure) and drive fluid and sodium loss when glucose exceeds ≈150 mg/dL 41, 42, 43, 44. In the current study, as shown previously, myostatin deletion increases muscle mass and reduces plasma glucose levels significantly 25.…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with the National Kidney Foundation guidelines (5), this has led the American Diabetes Association to recommend the screening of CKD in diabetic patients based both on the AER (threshold: 30 mg/24 h) and the Cockcroft and Gault equation or modification of diet in renal disease (MDRD) equation estimated GFR (threshold: 60 ml/min per 1.73 m 2 ) (6). The MDRD equation is superior to the Cockcroft and Gault equation: it is more accurate (7,8), more robust when glucose control is poor (9), and not biased by body weight (10), which is of considerable importance because of the frequent association of type 2 diabetes, and CKD (11), with obesity. Most of the recent reports on CKD in diabetic patients rely on MDRD e-GFR (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%